رابطة شباب جنوب إفريقيا التشكيل التنظيمي والبناء الفكري والعقائدي 1918-1948 (Journal of the College of Basic Education, 2024)
This association is considered a unique model among the extremist Christian political movements in Africa. It is a secret association that works to dominate Afrikaner nationalism in South Africa, by preserving their history, culture and language. It represents the far right of the extreme, as it worked to politicize religion to achieve political ends, so it tried The Association, as an extremist religious-political group, imposed its ideas and doctrine on those around it from an elitist standpoint, giving itself the right to think and make decisions on behalf of others for the benefit of certain elites, promoting its own interests using religious text and intellectual doctrine under the claim that they have the knowledge and faith that authorize them to choose human destinies. Imposing their interpretations of the religious text on others, especially the simple ones. The study reached a number of conclusions, including: The Association is the true face of Christian religious terrorism in South Africa, and it also represents the true meaning of the concept of the deep state, especially its use of religious sentiment to contain minds, in order to achieve its goals of controlling the economy and politics.